THE INFLUENCE OF COMPENSATION, CAREER DEVELOPMENT, AND EMPLOYEE EMPOWERMENT ON ORGANIZATIONAL COMMITMENT AT PT PLN (PERSERO) UP3 YOGYAKARTA - Puspaningrum, Rr. Faizah Nur F; Septyarini, Epsilandri; Purnamarini, Tri Ratna (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
Human Resources (HR) are critical to a company's success as their expertise facilitates organizational growth. A key determinant of organizational performance includes employee commitment, which reflects their loyalty and willingness to stay with the company. The purpose of this study is to identify how compensation, career development, and employee empowerment affect commitment to the company. The method used in this research uses quantitative research using saturated sampling techniques. The research data was collected using a questionnaire, analyzed using computer assistance and the SPSS version 25 application. In this study, a saturated sampling technique was used with 45 respondents as members of the population. This research was conducted at PT PLN (Persero) UP3 Yogyakarta. The results revealed that compensation and career development have a positive and significant influence on organizational commitment. However, employee empowerment does not have a significant impact. Suggestions for future researchers in this field are expected to pay further attention to various variables that can affect organizational commitment. Those variables may include individual components, such as job satisfaction, motivation, and employee welfare. organizational components, such as corporate culture, leadership, and reward systems as well as changes in the industry, such as government policies and technological trends.